The effect of SMAD4 on the prognosis and immune response in hypopharyngeal carcinoma - Song, Juanjuan; Wu, Jialing; Ding, Jiaxuan; Liang, Yangxin; Chen, Changlong; Liu, Yimin (Frontiers in Medicine, 2023)
Objectives In malignant tumors, elevated infiltration of intratumoral CD8+ cytotoxic T cells predicts a beneficial prognosis, whereas high levels of CD15+ neutrophils in peritumor tissues indicate poor prognosis. It is unclear how SMAD4, which promotes favorable clinical outcomes and antitumor immunoregulation, along with CD8+ cytotoxic T cells and CD15+ neutrophils exert an influence on hypopharyngeal carcinoma (HPC). Materials and methods Specimens were collected from 97 patients with HPC. Immunohistological analyses of SMAD4, CD8+ cytotoxic T cell and CD15+ neutrophil expression were performed. SMAD4 nuclear intensity was measured, meanwhile, CD8+ cytotoxic T cells and CD15+ neutrophils were counted under a microscope. The prognostic role of SMAD4 was determined using the log-rank test and univariate and multivariate analyses. The relationship among SMAD4, CD8+ cytotoxic T cells, and CD15+ neutrophils was estimated by Mann–Whitney U test. Results High levels of SMAD4 were associated with favorable overall survival (OS) and disease-free survival (DFS) in HPC. Multivariate analysis suggested that SMAD4 is an independent predictor of OS and DFS. A high density of intratumoral CD8+ cytotoxic T cells and low accumulation of CD15+ neutrophils in the peritumor area were associated with longer OS and DFS. Furthermore, SMAD4 was linked to the levels of intratumoral CD8+ cytotoxic T cells and peritumoral CD15+ neutrophils. Patients with high SMAD4/high intratumoral CD8+ cytotoxic T cells or high SMAD4/low peritumoral CD15+ neutrophils showed the best prognosis. Conclusion SMAD4, CD8+ cytotoxic T cell level, and CD15+ neutrophil level have prognostic value in HPC. SMAD4 is a promising prognostic marker reflecting immune response in HPC.